Addressing High School Dropouts with a Scalable Intervention : The Case of PODER - Avitabile, Ciro; Cuevas, Janina; de Hoyos, Rafael; Jamison, Julian C. (World Bank, Washington, DC, 2019)
Working with the Mexican Ministry of Education, this study piloted a scalable program to reduce high school dropout rates by focusing on socio-emotional skill development and mathematics tutoring. The intervention was evaluated through a randomized field experiment with more than 5,000 youths at 20 upper secondary schools in Mexico City. An intention-to-treat analysis finds some evidence that exposure to the Opportunities and Development to Avoid Risks Program increases socio-emotional skills, but no evidence that it improves math outcomes or future attendance. Likely explanations for these 0 results include low take-up and other process factors, which are document qualitatively, as well as heterogeneous treatment effects. In particular, an inverse-probability-weighted matching model is suggestive of an effect whereby some students participate actively in the program and drop out of school less often, while other students choose not to participate when given the option and actually drop out more as a result.